The protective role of epstein-barr virus (EBV) - specific cytotoxic T lymphocytes in immunocompromised hosts with EBV infection - Patcha Incomserb (Chulalongkorn University, 2012)
Thesis (M.Sc.)--Chulalongkorn University, 2004